Reliability and Quality of Complex Systems - A.N. Litvinov (Надежность и качество сложных систем)
Background. One of the effective ways to increase the vibration and impact resistance of electronic components and automation devices for special–purpose products is the complete or partial filling of electronic components with polymer compounds of various densities and stiffness. Materials and methods. The features of the technological process of pouring blocks are indicated, the main characteristics affecting the effectiveness of vibration protection by pouring blocks of devices are established. Results and conclusions. It is shown that it is necessary to construct regression equations that allow predicting their dynamic characteristics at the early stages of block design and ensuring optimal vibration damping of electronic blocks in real operating conditions.